Task-Building Cataract Surgery Curriculum for the PGY-2 Resident: From the Wetlab to the Operating Room - Laura Wayman (Association of American Medical Colleges, 2013)
Abstract This resource aims to help second-year ophthalmology resident build the skills necessary to perform tasks associated with cataract surgery. In the resource, cataract surgery is divided into a series of discrete surgical tasks. Not all residents will progress at the same rate; therefore, not all will master the educational objectives. The order of the lab sessions can be altered by the surgical instructor to accommodate the needs of the learner or the availability of materials, such as practice eyes and viscoelastic. For consistency, each resident works one-on-one with an attending surgeon one afternoon per week learning and practicing each of these tasks. That same resident works in the operating room with the same attending once per week a few days after the wet lab session. The learner is able to perform the task in the operating room once he or she has mastered the skill in the wet lab. The same attending and resident pair care for the patient during the postoperative period. This resource was developed in 2005 to gradually introduce our residents to cataract surgery early in their training. Since introducing this course to the first-year curriculum in our residency program, we have identified several other benefits. These include introducing residents, early in their career, to caring for the surgical patient, surgical techniques and intraoperative decision-making processes, reflective learning through the debriefing process, ordering practice eyes and disposing of biohazard waste, and the cost of doing surgery. As a result of this supervised curriculum, we have been able to introduce residents to microsurgery much earlier in the program without endangering the welfare of patients. Another important benefit from my perspective as a program director is the opportunity to develop a relationship with each of our residents very early in their training.